Identifikasi Cendawan Patogen pada Beberapa Kultivar Benih Kacang Tunggak (Vigna unguicullata L.) Berdasarkan Ketinggian Tempat yang Berbeda di Kabupaten Timor Tengah Utara - Elisabeth Buik Monemnasi (Fakultas Pertanian, Universitas Timor, 2020)
Cowpea plant (Vigna unguiculata L.) is one of the legume plants. Physiologically, this plant has a fairly high level of adaptation, both in low and high altitudes so that it becomes a tradition for the people of North Central Timor to continue to cultivate it. Yield of cowpea production in the North Central Timor region every year remains low due to environmental conditions and pathogenic fungus attacks in the storage process that is not quite right. This study aims to determine the types of pathogenic fungi that attack, the resistance of varieties and the influence of altitude on pathogenic activity. The research was conducted in September to October in the Laboratory of the Faculty of Agriculture and Biology Laboratory, University of Timor. The study design uses a completely randomized design (CRD) with 2 factorial patterns, the first factor is the seed variety and the second factor is the area. Each treatment was repeated 3 times so that there were 27 experimental units. Observation of pathogen identification was carried out by morphological characterization, and seed viability viability testing was carried out using the UKDdp method. The observational data were then analyzed using a completely randomized design (ANOV) variance and further tested using the Duncan Multiple Range Test (DMRT) with a significant level of 5%. Based on research that has been conducted, that there are five contaminant fungi contaminating red, white, black varieties of cowpea from several regions in the TTU region, including Fussarium sp, Fungi Melanospora sp, Fungi Collectotrichum sp, Fungi Aspergillus sp, and Fungi Altenaria sp. The biggest attack was caused by the fungus Fussarium sp.